Polyculture and Monoculture Affect the Fitness, Behavior and Detoxification Metabolism of Bemisia tabaci (Hemiptera: Aleyrodidae) - Di, Ning; Zhang, Kai; Zhang, Fan; Wang, Su; Liu, Tong-Xian (Frontiers in Physiology, 2018)
Herbivores respond differently to the level of plant diversity encountered. Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) are highly polyphagous herbivores which cause considerable damage to various crops. Herein, we reared this species both in polyculture and monoculture, including preferred and less preferred host plants such as Chinese cabbage (Brassica rapa L.), tomato (Solanum lycopersicum L.), kidney bean (Phaseolus vulgaris L.) and summer squash (Cucurbita pepo L.). Trends in survival and oviposition were recorded, and impact of plants on growth and development of B. tabaci were studied, particularly in terms of detoxification and digestive enzymatic activity in the insects. We found that the survival rate was the highest in Chinese cabbage monoculture treatment. Further, the egg numbers on individual species in the polyculture generally reflected numbers on the same plant species in monoculture. However, more eggs were observed in each of the four plant species tested in the context of polyculture. The activity of superoxide dismutases (SOD) and alkaline phosphatase (AKP) in B. tabaci fed in a choice situation were significantly lower than those fed with tomato monoculture, indicating a dilution of toxicity with a multi-plant diet compared with less preferred host plant diet. Also, the survival rate of B. tabaci in monoculture was negatively correlated with SOD amount of whitefly. In the plants attacked by whiteflies, the activity of polyphenol oxidase (PPO) and catalase (CAT) in Chinese cabbage was lower in polyculture than in the monoculture. These results implied that multi-plant treatments contained fewer secondary metabolite substances and might be less toxic to polyphagous herbivores. As such, the work herein contributes knowledge relevant for more effective control and management of B. tabaci.